A comparative study of laparoscopic (LC) vs. open cholecystectomy (OC) in a medical school of Bihar, India - Ranjan, Rajiv; Sinha, Kishore K.; Chaudhary, Mahesh (International Journal of Advances in Medicine, 2018)
Background: Gallstone disease is a significant health problem world over (in both developing and developed nations). The incidence of gallstone disease increases after age of 40years and it becomes 4-10 times more common in old age. As many as 16% and 29% of women above the age of 40-49 years and 50-59 years, respectively, had gall stones. Laparoscopic cholecystectomy introduced in 1985 has become the procedure of choice for surgical removal of the gallbladder. The aim is to compare laparoscopic cholecystectomy and open cholecystectomy in patients of cholelithiasis by measuring parameters such as use of post-operative analgesia, operative time, post-operative hospital stays, morbidity, mortality and patient satisfaction. Methods: It is a prospective randomized study of 120 patients of cholelithiasis aged between 20years to 80years operated during 2015-2018 at of Anugrah Narayan Magadh Medical College and Hospital, Gaya, Bihar, India. They were divided into open and laparoscopic Cholecystectomy groups by drawing a lottery. Results: The median (range) operation time for laparoscopic cholecystectomy was 55-155 min (mean=102 min) and 40-105 min (mean=72 min) for open cholecystectomy (p <0.001). Form LC group 5 cases had to be converted to OC. Rate of conversion was 5/60=8.3% which is within limits of worldwide laparoscopic cholecystectomy conversion rate of 5% to 10%. LC was found to be superior to OC. Conclusions: Laparoscopic cholecystectomy is better than open cholecystectomy However, open cholecystectomy is preferable in cases of complicated cholecystectomy.